1987
DOI: 10.1007/bf02546268
|View full text |Cite
|
Sign up to set email alerts
|

Retro‐aldol degradations of unsaturated aldehydes: Role in the formation ofc4‐heptenal fromt2,c6‐nonadienal in fish, oyster and other flavors

Abstract: Alterations of cucumber‐, melon‐like notes in aromas and flavors caused by retro‐aldol degradations oft2,c6‐nonadienal were confirmed using gas chromatographic measurements of volatile compounds in model systems. The data indicated that 3‐hydroxy‐c6‐nonenal was formed first by the addition of water to the alpha/beta double bond oft2,c6‐nonadienal, and this was followed by a retro‐aldol condensation of 3‐hydroxy‐c6‐nonenal to yieldc4‐heptenal and ethanal. Compared to the reaction rate in aqueous systems at neut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
64
0
2

Year Published

1990
1990
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 26 publications
2
64
0
2
Order By: Relevance
“…It was detected in fish oil [18,26] and fish oil-enriched mayonnaise [22] but was found to be absent after the frozen storage of salmon [19]. The absence of 4-(Z)-heptenal during the oxidation process suggested that retro-aldol degradation from the conversion of 2, 4-(E,Z)-nonadienal to yield this volatile, as proposed elsewhere [34], did not occur. On the basis of PV, AV and 1-penten-3-one determinations (Fig.…”
Section: Oxidative Stability Of the Oilmentioning
confidence: 69%
“…It was detected in fish oil [18,26] and fish oil-enriched mayonnaise [22] but was found to be absent after the frozen storage of salmon [19]. The absence of 4-(Z)-heptenal during the oxidation process suggested that retro-aldol degradation from the conversion of 2, 4-(E,Z)-nonadienal to yield this volatile, as proposed elsewhere [34], did not occur. On the basis of PV, AV and 1-penten-3-one determinations (Fig.…”
Section: Oxidative Stability Of the Oilmentioning
confidence: 69%
“…However, these workers were unable to account for the presence of cis-4-heptenal by accepted autoxidation mechanisms. Josephson and Lindsay (1987) discovered that the retro-aldol condensation of trans-2,cis-6-nonadienal resulted in the formation of cis-4-heptenal, and thus accounted for its close association with lipid oxidation and cooking where its formation is greatly accelerated. Although cis-4-heptenal does not appear to possess a fishy flavour, it causes a pronounced potentiation of the fishiness contributed by the 2,4,7-decatrienals (Karahadian and Lindsay, 1989).…”
Section: Deterioration Of Fish Flavoursmentioning
confidence: 98%
“…It is the retro-aldol condensation product of 2,6-nonadienal, which is also listed in Table 3. This latter compound, strongly reminiscent of cut cucumber, is in turn an oxidation product of linolenic acid (Josephson & Lindsay 1987a, 1987b. These researchers found that 4-heptenal was the dominant off-odour in reheated boiled potatoes.…”
Section: Possible Causes Of Pastoral Flavourmentioning
confidence: 99%